Penerapan E-Voting Dalam Pemilihan Ketua OSIS Di SMA Negeri 1 Geyer Kabupaten Grobogan - Ferdianto, Raditya; Kuswardono, Danang; Tanuji, Hadi; Pratondo, Katon; Assiva, Muhammad Amry (Lembaga Penelitian Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2025)
This report presents the results of community service activities carried out by the Muhammadiyah Grobogan Institute of Technology and Business, focusing on the application of e-voting applications in the election of student council chairman at SMA Negeri 1 Geyer, Grobogan Regency. This community service explains the importance of technology in improving efficiency and transparency in the election process, as well as the challenges faced by conventional election systems. The method used includes several stages, namely preparation, socialization, training, implementation, and evaluation. Preparation includes designing the e-voting program and procuring the necessary tools. Socialization was conducted through simulations to students and teachers to introduce the e-voting application. Training was given to the election committee so that they could use the system properly. Results showed that the implementation of e-voting accelerated the vote counting process and increased student participation and trust in the election system, making this activity an innovative step in school democracy.